Dampak Pemasaran Digital terhadap Pembelian Skincare: Sinergi Promosi Media Sosial, Ulasan Online, Harga, dan Kualitas Pelayanan - Oktavia Ayu Lestari; Aqmala, Diana; Taufan Hariyadi, Guruh; Yovita, Lenni (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
The skincare industry in Indonesia continues to grow rapidly, but Natasha Skincare faces challenges in the form of declining sales from 2020-2024. Competition in this industry is getting tighter due to the emergence of many new clinics, so purchasing decisions are an important factor in maintaining a business. This study aims to determine the extent to which social media promotions, online customer reviews, prices, and service quality influence Natasha Skincare purchasing decisions. This study uses quantitative techniques with 100 respondents, selected based on predetermined criteria (Purposive sampling), and filling out an online questionnaire sent via G-form. The data was then analyzed using IBM SPSS 26 which includes descriptive analysis, validity and reliability tests, classical assumptions, multiple linear regression, hypothesis testing, and coefficient of determination. The findings of this study indicate that social media promotions, online reviews, prices, and positive service quality significantly influence purchasing decisions. This study shows that Natasha Skincare needs to improve its social media promotion strategy, maintain positive online customer reviews, offer competitive prices, and ensure quality service. With the skincare industry facing intense competition, it is important to expand sales and maintain competitiveness amidst increasingly competitive competition.